Morbidity profile and outcome of neonates admitted in a secondary level SNCU in district Udhampur in Jammu and Kashmir - Kumar, Deepak; Gupta, Sonika (International Journal of Contemporary Pediatrics, 2021)
Background: Infant mortality is an important indicator of healthcare system of the country and neonatal mortality contributes a major proportion to infant mortality. So this study was undertaken to study the demographic and morbidity profile and outcome of neonatal care in our area. Methods: This study, a retrospective observational study was conducted in district hospital Udhampur which caters to a population of around 5.5 lakh. Case records of all SNCU (special newborn care unit) admissions between January 2018 to December 2018 were analysed in a pre-designed proforma which included identity, clinical and demographical variables, admitting complaints, diagnosis, treatment, hospital stay and outcome. Results: Of the total 364 neonates with an average birth weight of 2.67 kgs, 70.60% were of weight over 2.5 kg. The most common diagnosis included sepsis (27.74%), neonatal hyperbilirubinemia (13.18%) and RDS (respiratory distress syndrome) (10.43%). Discharge rate was 60.71% with mortality of 3.26% and referral rate of 31.31%. Conclusions: Sepsis and RDS as the most common cause of morbidity in our setup indicate that improvement in community as well as hospital hygiene along with improved antenatal care and maternal health needs to be stressed upon to prevent them.